2020
DOI: 10.4103/jpbs.jpbs_129_20
|View full text |Cite
|
Sign up to set email alerts
|

Detection of salivary alkaline phosphatase levels in smokers, diabetic patients, potentially malignant diseases and oral malignant tumours

Abstract: A BSTRACT Aim: Alkaline phosphatase (ALP) is present in human and plays a key role in intracellular destructive processes and cellular damage. It has bicarbonate and phosphate ions, which help in buffering against acids. ALP activity is affected by smoking, which changes pH in oral environment and has harmful effects. Thus, the evaluation of ALP activity of smokers and healthy nonsmoker along with patients who were diabetic, potentially malignant, and malignant was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…[ 24 ] Almost all of the previous studies have shown increased ALP levels due to inflammation in smokers with diabetes. [ 4 13 14 ] However, the trend is contradictory to the findings of our study revealed lower ALP levels in smokers with diabetes. This may be due to the combined effect of the smoking habit in diabetic conditions have suppressed the immune system that reduced the production of ALP in smokers with diabetes.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…[ 24 ] Almost all of the previous studies have shown increased ALP levels due to inflammation in smokers with diabetes. [ 4 13 14 ] However, the trend is contradictory to the findings of our study revealed lower ALP levels in smokers with diabetes. This may be due to the combined effect of the smoking habit in diabetic conditions have suppressed the immune system that reduced the production of ALP in smokers with diabetes.…”
Section: Discussioncontrasting
confidence: 94%
“…[ 9 ] Owing to diabetes, damaged cells of periodontal tissues consistently release ALP into the gingival crevicular fluid (GCF) and saliva. [ 4 6 ] Previous studies have shown significantly increased levels of GCF, serum, and salivary ALP in chronic periodontitis,[ 6 8 9 10 11 ] smokers and tobacco chewers with diabetes,[ 4 9 11 12 13 14 ] and oral malignant diseases. [ 4 11 13 ] Among these, few studies have been conducted, mostly in smokers with diabetes and periodontitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALP can be a salivary biomarker of periodontal diseases and caries ( 46 ), as it interferes in the balance of the remineralization-demineralization cycle since it is primarily involved in calcium and phosphate binding ( 47 ). It seems that the function of ALP relatively depends on the salivary pH and buffering capacity ( 48 ). Khalighefar et al ( 28 ) reported that ALP rebounds during the middle of Ramadan compared to BR.…”
Section: Discussionmentioning
confidence: 99%
“…So ALP levels in the serum may be an effective biomarker in medical diagnosis [ 9 , 10 , 11 ]. Furthermore, Prakash et al have recently found that the level of ALP in saliva (readily accessible, safe, and noninvasive body fluid) may be able to serve as an early biomarker for diabetes mellitus and some potentially malignant tumors [ 12 ]. In addition, ALP is capable of generating signals for the analytes by conjugating to streptavidin or the second antibody in the biological analysis, such as enzyme-linked immunosorbent assay (ELISA), histochemical staining, and aptamer-based assay [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%